A Europe of courts, a Europe of factions
1 online resource (ix, 263 pages)
Keywords: In A Europe of Courts, a Europe of Factions the contributors offer an analysis of the political groups of the most representative European courts of the sixteenth and seventeenth centuries. Transcending individual cases, this collection presents the first comparative overview of the phenomenon of court factionalism. Through original research and a critical approach, González Cuerva and Koller explore in depth the emergence, coexistence and image of court factions. This contribution to the debate on the nature of early modern policy-making is enriched with a European-wide focus, which allows comparison of the circumstantial and micropolitical factors accounting for the spread of factions and the conditions in which they functioned. It also allows partisan sources to be examined with the necessary caution. Contributors are Stefano Andretta, Janet Dickinson, Luc Duerloo, Pavel Marek, José Martínez Millán, Toby Osborne, David Potter, Jonathan Spangler, Evrim Türkçelik, and Maria Antonietta Visceglia.